2011
DOI: 10.1073/pnas.1018941108
|View full text |Cite
|
Sign up to set email alerts
|

A cyclin-D1 interaction with BAX underlies its oncogenic role and potential as a therapeutic target in mantle cell lymphoma

Abstract: The chromosomal translocation t(11;14)(q13;q32) leading to cyclin-D1 overexpression plays an essential role in the development of mantle cell lymphoma (MCL), an aggressive tumor that remains incurable with current treatment strategies. Cyclin-D1 has been postulated as an effective therapeutic target, but the evaluation of this target has been hampered by our incomplete understanding of its oncogenic functions and by the lack of valid MCL murine models. To address these issues, we generated a cyclin-D1-driven m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 28 publications
1
47
2
Order By: Relevance
“…Establishment and characterization of mouse lymphoma models of resistance to To ascertain whether ABT-199 might induce mutations in target proteins and thus confer therapeutic resistance, we chose MCL as a model disease, because this aggressive cyclin-D1-expressing B-cell lymphoma frequently shows constitutive expression of BCL2 and responds to 27 We used human-like MCL cell lines developed by stably coexpressing cyclin-D1 and Bcl2 in mouse B lymphocytes (supplemental Figure 1). 27 Two mouse cell lines, LyBcl2-6 and LyBcl2-9, were cultured with increasing concentrations of ABT-737, followed by sustained exposure to ABT-199 for 5 months ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Establishment and characterization of mouse lymphoma models of resistance to To ascertain whether ABT-199 might induce mutations in target proteins and thus confer therapeutic resistance, we chose MCL as a model disease, because this aggressive cyclin-D1-expressing B-cell lymphoma frequently shows constitutive expression of BCL2 and responds to 27 We used human-like MCL cell lines developed by stably coexpressing cyclin-D1 and Bcl2 in mouse B lymphocytes (supplemental Figure 1). 27 Two mouse cell lines, LyBcl2-6 and LyBcl2-9, were cultured with increasing concentrations of ABT-737, followed by sustained exposure to ABT-199 for 5 months ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The fragment coding amino acids 1 to 204 of mBcl2 (lacking transmembrane domain) was obtained by standard PCR using the pBABE-puro-mBCL2 plasmid as template 27 and then was subcloned into the expression vector pETM-14 using the GIBSON Assembly Cloning Kit (New England BioLabs) according to the manufacturer's instruction. F101L and F101C mutants were generated using site-directed mutagenesis as describe above.…”
Section: Expression and Purification Of Murine Bcl2mentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 In MCL, it has been assumed that Cyclin D1 primarily acts through its role in the cell cycle, controlling the transition of G 1 to S phase by binding and activating cyclin-dependent kinase (CDK) 4 and CDK6 followed by phosphorylation of the retinoblastoma protein and release of the transcription factor E2F. 30 However, in other malignancies several CDK-independent functions of Cyclin D1 have been identified, including interaction with the pro-apoptotic protein BAX 21 and RAD51, 31 the latter impacting DNA repair.…”
mentioning
confidence: 99%
“…20 However, although Cyclin D1 is overexpressed in MCL, it has been shown that Cyclin D1 does not induce MCL development in vivo. 21 Furthermore, the lack of prognostic information related to Cyclin D1 22 and the existence of Cyclin D1 negative MCL (7%-15%) challenges the requisite of this protein for tumorigenesis. 18,23 Knockdown of Cyclin D1 has also been reported to only have a limited effect on cell proliferation and apoptosis.…”
mentioning
confidence: 99%